2021
DOI: 10.3390/nano11113012
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like SnO2 Nanoparticle Biofabrication Using Pometia pinnata Leaf Extract and Study on Its Photocatalytic and Antibacterial Activities

Abstract: The present study reported biofabrication of flower-like SnO2 nanoparticles using Pometia pinnata leaf extract. The study focused on the physicochemical characteristics of the prepared SnO2 nanoparticles and its activity as photocatalyst and antibacterial agent. The characterization was performed by XRD, SEM, TEM, UV-DRS and XPS analyses. Photocatalytic activity of the nanoparticles was examined on bromophenol blue photooxidation; meanwhile, the antibacterial activity was evaluated against Klebsiella pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Furthermore, spherical shaped Fe 2 O 3 NPs with diameter 51 nm were synthesized using Hibiscus rosa sinensis flower extract (Figure k . Flower like structures of tin dioxide (SnO 2 ) NPs in the size range 8–20 nm were synthesized using Pometia pinnata extract (Figure l) . Similarly, diverse shapes of Ag NPs such as tetrahedral, spherical, and oval with diameters of 32–77 nm were synthesized utilizing stem, leaves, and roots of Persicaria hydropiper extract as shown in Figure m–p …”
Section: Green Synthesis Of Metal/metal Oxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, spherical shaped Fe 2 O 3 NPs with diameter 51 nm were synthesized using Hibiscus rosa sinensis flower extract (Figure k . Flower like structures of tin dioxide (SnO 2 ) NPs in the size range 8–20 nm were synthesized using Pometia pinnata extract (Figure l) . Similarly, diverse shapes of Ag NPs such as tetrahedral, spherical, and oval with diameters of 32–77 nm were synthesized utilizing stem, leaves, and roots of Persicaria hydropiper extract as shown in Figure m–p …”
Section: Green Synthesis Of Metal/metal Oxide Nanoparticlesmentioning
confidence: 99%
“…(l) FESEM images of flower-like morphology of SnO 2 NPs synthesized using Pometia pinnata extract. Reproduced with permission from ref . Copyright 2021 MDPI publishers.…”
Section: Green Synthesis Of Metal/metal Oxide Nanoparticlesmentioning
confidence: 99%
“…The 3 nm-sized, highly photocatalytically active nanoparticles were synthesised; 88.8% of the 9 of 23 MB solution was degraded by SnO2 NPs after 30 minutes of UV light, and 90.0% after 120 minutes of UV irradiation. Pometia pinnata leaf extract was used by Fatimah et al [55] to biofabricate flower like SnO2 NPs. On the photooxidation of bromophenol blue (BPB), the nanoparticles' photocatalytic activity was investigated.…”
Section: Sc-i Sc-ii Sc-ii Sc-imentioning
confidence: 99%
“…The other major mechanistic ways in which NPs exhibit antibacterial behaviour are the deactivation of enzymes, their attachment to NPs, and the disruption of the hydrogen bonding between two antiparallel strands of DNA [101]. [55] for the biofabrication of flowers like SnO2 NPs. Antibacterial testing revealed that the synthesised SnO2 NPs exhibit an inhibition of the tested bacteria and have the potential to be used in other medicinal applications.…”
Section: Antimicrobial Activity Of Sno2 Nps/ Sno2 Based Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation